Effects of vitamin D3 (cholecalciferol) supplementation on systemic lupus erythematosus patients with hypovitaminosis D on serum pro-inflammatory cytokines (IL-6, IL-7, IFN-Gamma), anti-inflammatory cytokine (TGF-Beta) and anti-ds DNA levels - Cesarius Singgih Wahono; Irene Saveria; Cameleia Diah Setyorini; Zoraida Dwi Wahyuni; Handono Kalim; Kusworini Handono (Indonesian Rheumatology Association, 2020)
A B S T R A C TSystemic lupus erythematosus (SLE) is a chronic systemic autoimmune diseaseand can attack almost all organs and tissues of the human body. Beside geneticfactors, environmental factors are thought to play a role, such as ultraviolet light,viral infections and smoking, causing a breakdown of self-tolerance which cantrigger an autoimmune response. The study was conducted in the outpatient andinpatient units of the Rheumatology Division of the Department of InternalMedicine Saiful Anwar General Hospital/Faculty of medicine UniversitasBrawijaya, Malang. Subjects were female patients, aged > 18 years who had beendiagnosed as SLE by internist-rheumatologist based on the 1997 ACR criteria, withSLEDAI score > 3. After 3 months of supplementation, there was a significantdecrease in serum levels of the three pro-inflammatory cytokines (IL-6, IL-17, IFN-gamma), as shown in table 3, compared to before treatment, as well as anti-dsDNA levels.Serum TGF-beta1 levels increased significantly, while 25 (OH) D3 levels also increasedsignificantly.